Associated Professor, St. Claret College, Dept. of Commerce (PG), Bengaluru. - Jayanthi, M.; Bella, K Majini Jes; Bella, K Majini Jes (International Journal of Psychosocial Rehabilitation, 2020)
In this dynamic environment, employee performance management is more critical to any organization moreover it is very important to the industry. The success of an organization depends on the performance of the employee. So the organization should focus on their employee performance, they need ongoing performance improvement which fulfills the interests professionally and personally. Most of the organization's main aim is to improve employee performance by conducting various development programmes. This article deals with the effectiveness of the performance management system. This study concluded that strategies and policies improve the performance of the employee and the organization.